Sun Corals - A Resistant Invader: Assessment of the Acute Toxicity of Contaminants Associated with Petroleum and Petrochemical Activities on the Species Tubastraea coccinea - Fukushima, Letícia May [UNESP]; de Souza Abessa, Denis Moledo [UNESP]; Capel, Katia Cristina Cruz (My University, 2022)
The oil and petrochemical industry are an important source of pollution to the marine and coastal environments. Tropical and subtropical regions are particularly susceptible to the environmental impacts from oil spills, including possible effects to reef ecosystem, which are abundant within these areas. Brazil harbors a coral fauna considered unique in the world, which has been suffering from numerous environmental pressures, with many species currently threatened. Corals of the genus Tubastraea (Sun corals) are non-indigenous species on the Brazilian coast, which are becoming adapted to the local ecosystems. This study evaluated biological hazards of water soluble fractions (WSF) of fuel oil, marine diesel, samples of spilled oil in the NE, and the Aqueous Film Forming Foam (AFFF)-Agefoam 2133 on the species Tubastraea coccinea, through acute toxicity tests. The tests took place in triplicates, in which colonies with 9-30 polyps were exposed to contaminants for 96 hours. Organisms from the controls and most of the test-dilutions presented 100% survival, except for the highest concentrations of substances AFFF-Agefoam 2133, WSF from marine diesel, and the oil sample from the Northeast spill in 2019. The highest concentrations of AFFF and WSF of marine diesel showed significant effects compared to the control, being determined as the lowest-observed-effect concentration (LOEC) and the no-observed-effect concentration (NOEC), which were, 1% and 100% respectively. Other substances (WSF from NE oil slicks and bunker C fuel oil) did not cause significant deleterious and sublethal effects. The study provided the first information on the effects of these compounds on scleractinian corals in Brazil.